Education and Personnel Evaluation: A Review of Leading Journals for the Period 2003-2004 - Persaud, Nadini (Journal of MultiDisciplinary Evaluation, 2004)
This article provides a review of the research literature on teacher evaluation topics, including interviews, summative issues, international comparisons, screening, and teacher reactions. The research articles were published in 2003 and 2004 in a range of academic journals, such as the Journal of Personnel Evaluation in Education, Journal of Human Resources, Journal of Teacher Education, NASSP Bulletin, and Education Administration Quarterly.